Mechanical Behavior and In Vitro Corrosion of Cubic Scaffolds of Pure Magnesium Processed by Severe Plastic Deformation - Claudio L. P. Silva (MDPI AG, 2021)
Reports in the literature show that severe plastic deformation can improve mechanical strength, ductility, and corrosion resistance of pure magnesium, which suggests good performance for biodegradable applications. However, the reported results were based on testing of small samples on limited directions. The present study reports compression testing of larger samples, at different directions, in pure magnesium processed by hot rolling, equal channel angular pressing (ECAP), and high pressure torsion (HPT). The results show that severe plastic deformation through ECAP and HPT reduces anisotropy and increases strength and strain rate sensitivity. Also, scaffolds were fabricated from the material with different processing histories and immersed in Hank’s solution for up to 14 days. The as-cast material displays higher corrosion rate and localized corrosion and it is reported that severe plastic deformation induces uniform corrosion and reduces the corrosion rate.